1989
DOI: 10.1139/f89-241
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Characteristics of White Whale (Delphinapterus leucas) From Capture Through Extended Captivity

Abstract: For proper husbandry, it is important to sample the environment from which marine mammals for captivity are taken and to monitor the animals frequently over an extended period. Samples for microbiological analysis were collected from 20 beluga whales during capture in the Churchill River. Seven animals were retained in three U.S. aquaria with anal and blowhole cultures taken over a 945-d period. Bacteria isolated from whales at capture included many soil and water forms found also in environmental samples. Pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Achromobacter spp. belongs to the normal dermal microflora of teleosts (Horsley 1977) and has also been isolated from healthy white whales Delphinapterus leucas (Buck et al 1989). However, it has also been associated with dermal lesions in fish (Antychowicz & Rogulska 1985, Zheng et al 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Achromobacter spp. belongs to the normal dermal microflora of teleosts (Horsley 1977) and has also been isolated from healthy white whales Delphinapterus leucas (Buck et al 1989). However, it has also been associated with dermal lesions in fish (Antychowicz & Rogulska 1985, Zheng et al 1991.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of S. agalactiae and L. garvieae from a wild marine mammal may have multiple implications for the epidemiology of these organisms in wild and captive animals and their transmission between species. Streptococcal species have been cultured from a number of marine mammal organs, such as the skin, blowhole, trachea, lungs, pharynx, and uterus; these organs may provide clues into the routes of entry (Higgins et al, 1980;Buck et al, 1989;Henton et al, 1999;Bonar and Wagner, 2003). Infections of streptococci are known to occur after ingestion of materials containing streptococcal organisms (Minami, 1979;Bromage and Owens, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple streptococcal species have been isolated, including Streptococcus iniae from captive Amazon river dolphins (Inia geoffrensis) (Pier and Madin, 1976;Bonar and Wagner, 2003); Streptococcus equi in North Atlantic pilot whales (Globicephala melaena) (Higgins et al, 1980); Streptococcus mitis from beluga whales (Buck et al, 1989); Streptococcus phocae from harbor seals (Phoca vitulina), grey seals (Haliochoerus grypus) (Skaar et al, 1994), and fur seals (Aretocephalus pusillus pusillus) (Henton et al, 1999); Streptococcus dysgalactiae subsp. dysgalactiae from harbor porpoises (Phocoena phocoena) (Swenshon et al, 1998); Streptococcus zooepidemicus and several unspeciated b-hemolytic Streptococcus sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accurate interpretation of blowhole air cultures as a screening test would require information on the prevalence of the respiratory tract fungi of healthy whales and the normal variation of test results in the target populations. Buck et al [1989] did serial blowhole cultures on a group of belugas from capture through 2.5 years in captivity. This study revealed three key findings.…”
Section: Discussionmentioning
confidence: 99%